Kosmopolitanisme Kesultanan Aceh Darussalam: Pusat Perekonomian, Kebudayaan, dan Ilmu Pengetahuan - Miswari, Miswari (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2024)
This study aims to understand the development of the Aceh Darussalam Sultanate, from its establishment and socio-cultural conditions to the factors contributing to its decline. It also seeks to uncover the role of the Aceh Sultanate in shaping Islamic identity in the Nusantara. The research employs historical methods with a descriptive-analytical approach. Data were collected from primary and secondary sources, such as manuscripts, historical documents, and previous academic studies. Analysis was conducted to identify the social, political, and religious dynamics within the Aceh Darussalam Sultanate. The Aceh Sultanate reached its peak during the reign of Sultan Iskandar Muda (1607–1636), who successfully expanded its territory and established global diplomatic relations. Aceh was renowned as a center of maritime trade and Islamic education with significant contributions from scholars such as Hamzah Fansuri and Syamsuddin Al-Sumatrani. However, internal conflicts, merchant dominance, and colonial intervention, particularly by the Portuguese and the Dutch, led to the Sultanate’s decline. The flourishing philosophical sufism was later replaced by a more conservative Sharia-based approach under the influence of scholars like Nuruddin Ar-Raniri. Despite these challenges, Aceh remains a symbol of Islamic grandeur in the Nusantara, with a lasting intellectual legacy.